Everolimus-eluting bioresorbable vascular scaffold (BVS) implantation in patients with ST-segment elevation myocardial infarction (STEMI) - Kajiya, T. (Toulouse, France; Europa Digital, 2016)
10.4244/EIJV9I4A80